Comparison of Prevalence of Shivering after Spinal Anaesthesia in patients undergoing Cesarean Section in Winter and Summer - Hafiz Wajih-Ul-Hassan, Syed Sajjad Raza Kazmi, Sabir Khan, Zulqarnain Butt, Shaheer Nayyar, Haleema Tahir, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Postoperative shivering is a common problem associated with spinal anesthesia. Shivering is usually triggered by hypothermia. This is by far the standard approach of anaesthesia for elective and emergency caesarean sections. Hypotension is the predominant complication during caesarean sections, linked to maternal nausea and vomiting, as well as the potential for fetal and neonatal acidosis. This study is being conducted as a part of quality improvement measure. Objective: To find the frequency of shivering after spinal anaesthesia in patients undergoing cesarean section in winter Study design: Descriptive case series Place and duration of study: Department of Anaesthesia, Jinnah Hospital, Lahore from 1st January 2022 to 30th June 2022. Methodology: There were two hundred patients registered. After undergoing spinal anesthesia, the patients were placed in the supine position, given 4 L/min of oxygen via a face mask, covered with surgical drapes without being actively warmed, and monitored using non-invasive arterial blood pressure measurements every five minutes, pulse oximetry, ECG (lead II and V with ST segment analysis), and core temperature monitoring. Patients were evaluated by an anesthesiologist for core temperature before and immediately after the intrathecal injection. Patients were followed were followed for 15 min after spinal anesthesia and shivering was recorded. Administration of spinal anesthesia and collection of data in the operation theater regarding the grade of shivering and efficacy of the drug was done by an anesthetist having 5 years of experience. Results: The average age was 26.33±7.47 years and the mean body mass index was 24.79±2.95 kg/m2. The shivering was found in 107(53.50%) patients. Conclusion: The frequency of shivering is 53.50% after spinal anaesthesia in patients undergoing cesarean section in winter. Keywords: Spinal anaesthesia, Cesarean section, Shivering.